El cheque protestado por insuficiencia de fondos, estudio del proceso de exigencia del cumplimiento de la obligación. - Merino Cortez, Kevin Vinicio (Machala : Universidad Técnica de Machala, 2015)
En el presente trabajo de investigación, he desarrollado una teoría muy importante en respuesta al caso propuesto, el mismo que tiene como tema central de discusión. EL CHEQUE PROTESTADO POR INSUFICIENCIA DE FONDOS, ESTUDIO DEL PROCESO DE EXIGENCIA DEL CUMPLIMIENTO DE LA OBLIGACION. Es así, que hemos hecho un recorrido de análisis sobre la reseña histórica del Cheque como el producto de la imaginación que han tenido que desplegar los comerciantes para solucionar sus necesidades cotidianas, el Cheque como título de crédito está condicionado por la existencia de dos necesidades compartibles, pero diferentes y que son la necesidad de guardar y la necesidad de utilizar. Y hemos analizado el estudio de la exigencia del cumplimiento de la obligación en el caso de estudio como es José gira un cheque de su cuenta corriente de Banco Pichincha a favor de Luis, por la suma de 5.000,00 USD., con fecha 15 de octubre de 2015. ¿Qué procedimiento debe seguir para cobrar su dinero si es que José se presentó al cobro el día 18 de Octubre y la cuenta no tenía fondos?
In this research, I have developed a very important event in response to the proposed theory, the same central theme of discussion. CHEQUE protested insufficient funds, study of the process of enforcement of the obligation. Thus, we have made a tour of analysis of the historical background of the check as the product of the imagination that had to deploy traders to solve their everyday needs, check the title of credit is conditioned by the existence of two shareable needs but different and that is the need to save and the need to use. And we have analyzed the study of the enforcement of the obligation in the case study as José write a check from your checking account to Banco Pichincha in favor of Luis, in the amount of $ 5,000.00., Dated 15 October 2015. What procedure should be followed to collect their money if Joseph was presented for payment on October 18 and has had no funds?In this research, I have developed a very important event in response to the proposed theory, the same central theme of discussion. CHEQUE protested insufficient funds, study of the process of enforcement of the obligation. Thus, we have made a tour of analysis of the historical background of the check as the product of the imagination that had to deploy traders to solve their everyday needs, check the title of credit is conditioned by the existence of two shareable needs but different and that is the need to save and the need to use. And we have analyzed the study of the enforcement of the obligation in the case study as José write a check from your checking account to Banco Pichincha in favor of Luis, in the amount of $ 5,000.00., Dated 15 October 2015. What procedure should be followed to collect their money if Joseph was presented for payment on October 18 and has had no funds?
Keywords: CHEQUE; PROCESO; PROTESTADO; CUMPLIMIENTO